22a. Answer: y' = 90x + 33
Explanation:
y = 5u² + u - 1 u = 3x + 1
First take the derivative of y = 5u² + u - 1 with respect to u
![\bigg((dy)/(du)\bigg)](https://img.qammunity.org/2020/formulas/mathematics/college/u84szeajhadxticye99ql22ieke2ydksio.png)
y' = (2)(5u)(u') + (1)(u') - 0
= (10u)u' + u'
Next, take the derivative of u = 3x + 1 with respect to x
![\bigg((du)/(dx)\bigg)](https://img.qammunity.org/2020/formulas/mathematics/college/256ktwo040c63f9ww5rx3k0o3frveyoozc.png)
u' = 3 + 0
u' = 3
Now, input u = 3x + 1 and u' = 3 into the y' equation:
y' = (10u)u' + u'
= 10(3x + 1)(3) + 3
= 30(3x + 1) + 3
= 90x + 30 + 3
= 90x + 33
***********************************************************************
22b. Answer:
![\bold{y'=-(4)/((2x+3)^(3))}](https://img.qammunity.org/2020/formulas/mathematics/college/h2748y5hmly96359mr52x3yy37hhhdehqt.png)
Explanation:
u = 2x + 3
![\text{We can rewrite y as }y=u^(-2)\\\text{Take the derivative of }y=u^(-2)\text{ with respect to u}\ \bigg((dy)/(du)\bigg)\\\\y'=(-2)(u^(-3))(u')](https://img.qammunity.org/2020/formulas/mathematics/college/fbikgigdbfps2k4pboz08g9fne6cj1oa26.png)
Next, take the derivative of u = 2x + 3 with respect to x
![\bigg((du)/(dx)\bigg)](https://img.qammunity.org/2020/formulas/mathematics/college/256ktwo040c63f9ww5rx3k0o3frveyoozc.png)
u' = 2 + 0
u' = 2
Now, input u = 2x + 3 and u' = 2 into the y' equation
![y'=(-2)(2x+3)^(-3)(2)\\\\y'=-4(2x+3)^(-3)\\\\y'=-(4)/((2x+3)^(3))](https://img.qammunity.org/2020/formulas/mathematics/college/weitckddvkrsx7k9resoc227eeesqihspa.png)